Negotiating Autonomy: Art Workers, Media, and the Cultural Industries in Indonesia - Rianto, Puji; Wahyuni, Hermin Indah; Wahyono, Sugeng Bayu (Universitas Semarang, 2025)
Purpose: This study investigates the autonomy of art workers within the Indonesian cultural industry through a case study of two local television stations, ADiTV and Bali TV. The main objective is to examine how art workers maintain their autonomy while navigating the demands of the market and the organizational values imposed by their institutions. Methods: This study adopts a qualitative case study approach. Data were collected through in-depth interviews with television managers, art workers, and observers. The observers interviewed in this study were individuals with a deep and long-standing concern for the dynamics of local television. ADiTV and Bali TV were selected as research sites due to their distinctive characteristics. ADiTV operates as a local television channel with an Islamic missionary orientation, while Bali TV is embedded within the Ajeg Bali cultural movement. Findings: This study found that the autonomy of art workers in the cultural industry on local television shows a negotiated position. This study found that economic interests in pursuing profits and mass production within the cultural industry do not always harm the autonomy of art workers. Pressures on art workers actually come from non-market forces that are more cultural, such as Islamic values ​​on ADiTV or Ajeg Bali on Bali TV. Originality: This research contributes to the debate on artists' autonomy in the local television. By taking non-economic factors into account in determining artists' autonomy, this study makes an essential contribution to the discussion on artists' autonomy in the cultural industry, which tends to emphasize commercial factors.